2021
DOI: 10.1155/2021/8839897
|View full text |Cite
|
Sign up to set email alerts
|

Inflation Pressure in Side Branch during Modified Jailed Balloon Technique Does Not Affect Side Branch Outcomes

Abstract: Objectives. This study aimed to investigate the optimal jailed balloon inflation in the side branch during the modified jailed balloon technique for bifurcated lesions. Background. The modified jailed balloon technique is one of the effective techniques to minimize the emergence of side branch (SB) compromise by preventing plaque or carina shifting during a single stent strategy in the main vessel with provisional SB treatment. However, there are no detailed studies on the method of optimal jailed balloon infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…However, JWT is favored for its lower rates of dissection in clinical practice. In the literature, JBT has been shown to increase the risk of dissection, especially when the jailed balloon is inflated [ 19 , 20 ]. Since these reports were single-arm studies, they were not enrolled in this review.…”
Section: Discussionmentioning
confidence: 99%
“…However, JWT is favored for its lower rates of dissection in clinical practice. In the literature, JBT has been shown to increase the risk of dissection, especially when the jailed balloon is inflated [ 19 , 20 ]. Since these reports were single-arm studies, they were not enrolled in this review.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study in Japan also demonstrated that the inflation pressure of the jailed balloon did not affect SB outcomes. However, the balloon size used in MB is larger than that used in SB and the sample size was small, which would not be appropriate for all bifurcation lesions 18 …”
Section: Discussionmentioning
confidence: 99%
“…However, the balloon size used in MB is larger than that used in SB and the sample size was small, which would not be appropriate for all bifurcation lesions. 18 Kumsars et al reported that the final kissing balloon inflation had no benefit in reducing the incidence of SB stenosis-related ischemia after MB stent implantation. 19 There are also studies showing that ostial stenosis of the SB determined by quantitative coronary angiography could not predict the functional significance of the SB (flow fraction reserve value) after MB stent deployment.…”
Section: 2%mentioning
confidence: 99%
“…Nomura et al . [ 56 ] showed that SB balloon pressure, or stent balloon nominal pressure did not affect procedural outcomes. However, SB dissection occurred in 14 of the 51 patients, SB flow less than TIMI 3 occurred in 3 lesions, and SB ostial stenosis increased in 5 patients [ 56 ].…”
Section: Side Branch Protection Techniquesmentioning
confidence: 99%